Conservation of resources for sustainable performance in tourism - Rashid, Aamir; Rasheed, Rizwana; Albhirat, Muath Maqbool; Amirah, Noor Aina (Journal of Tourism Management Research, 2024)
This study aims to examine the impact of green purchasing, waste management, eco-friendly design of products and services, and customer relationship management on sustainable performance in the South Asian tourism industry. The contemporary tourism and hospitality industry increasingly focuses on environmental sustainability. The tourism sector is considered to contribute significantly to the economy. It allows employment and generates economic profits, resulting in an increase in overall economic activity. This study used deductive and quantitative approaches to evaluate the research hypotheses. Data was gathered from 463 tourism-related businesses situated across diverse locations in Pakistan. This study discovered that green purchasing has a significant impact on sustainable performance. Similarly, waste management, eco-friendly design of products and services, and customer relationship management all had a significant impact on sustainable performance. This research presents a framework that highlights the practices of tourism businesses in attaining sustainable performance, utilizing the Conservation of Resources (COR) theory for support. The inclusion of COR theory in examining variables related to sustainable performance is considered a unique and pioneering contribution to interdisciplinary fields such as supply chain management and the tourism industry. Furthermore, this study is the first of its kind in the South Asian region, specifically in Pakistan.